Geographical Multicast Disruption Tolerant Networking Mechanism For Internet Of Things - Wong, Khang Siang (2022)
Disruption Tolerant Networking (DTN) has been developed to overcome the intermittent connection issue between nodes in areas with poor wireless network connectivity by employing a store-carry-forward paradigm to forward messages to the destination. The existing networking protocols such as Transmission Control Protocol (TCP) and User Datagram Protocol (UDP) are not suitable since there may never be an end-toend path between the sender and the receiver. As the Internet of Things (IoT) devices proliferate, enabling DTN support in IoT environments helps bridge the communication gap between networks with intermittent connectivity such as rural areas and postdisaster scenarios. Group communication is an essential service to enable information exchange and sharing within a group and between groups in such networks. Furthermore, some applications require reliable multicast support over resource-constrained DTN networks. However, there is no well-defined standard for efficient and reliable group communication in DTN. The group communication in a post-disaster scenario that covers a large geographical area presents a more challenging environment for the disaster relief personnel to communicate and coordinate search and rescue missions. A group-based data delivery service is needed in DTN networks with multicast support for communication over multiple geographical areas. In resource-constrained IoT networks, the group-based data delivery needs to be enhanced to provide reliable multicast support for use cases, such as reliable configuration updates.